النسق القيمي للمرأة العاملة وعلاقته بالولاء الوظيفي - لمادي، حليمة (جامعة الوادي university of Eloued, 2020)
الملخص: تهدف هذه الدراسة الى معرفة طبيعة العلاقة بين الولاء الوظيفي والنسق القيمي للمرأة العاملة عن طريقة ميدانية على عينة العاملات ببلدية قمار وفروعها، وقد تم الاعتماد على المنهج الوصفي والاحصائي، وقد طبقت الدراسة على 33 عينة وقد تم تحليل الاستبيان ببرنامجspss ، وقد توصلت الدارسة الى العديد من النتائج أهمها وجود علاقة ذات دلالة احصائية بين النسق القيمي والولاء الوظيفي للعاملين في مؤسسة البلدية (الهيئة العمومية بلدية قمار وفروعها). Abstract This study aims to know the nature of the relationship between job loyalty and the value pattern of working women through a field method on the sample of female workers in Guemar municipality and its branches, and the descriptive and statistical approach has been relied upon, the study was applied on 33 samples and the questionnaire was analyzed by the SPSS program, and the study reached many Among the results, the most important of which is the existence of a statistically significant relationship between the value system and the functional loyalty of the workers in the municipality institution (the General Authority of Guemar Municipality and its branches). ".
دراسة ميدانية على عينة العاملات ببلدية قمار وفروعها
مذكرة ماستر في علم الإجتماع تخصص تنظيم وعمل
Keywords: النسق القيمي، الولاء الوظيفي; Modèle de valeurs, fidélité fonctionnelle; Values pattern, functional loyalty